Somniosus microcephalus - Carneiro, Miguel; Martins, Rogélia; Landi, Monica; Costa, Filipe O. (Zenodo, 2014)
□ Somniosus microcephalus (Bloch & Schneider, 1801) – Greenland shark; Tubarão-da-Gronelândia ①② , ③ Published as part of Carneiro, Miguel, Martins, Rogélia, Landi, Monica & Costa, Filipe O., 2014, Updated checklist of marine fishes (Chordata: Craniata) from Portugal and the proposed extension of the Portuguese continental shelf, pp. 1-73 in European Journal of Taxonomy 73 on page 14, DOI:10.5852/ejt.2014.73, http://zenodo.org/record/3866515